A taste for locally produced food - Values, opinions and sociodemographic differences among 'organic' and 'conventional' consumers. (1st April 2020) - Ditlevsen, Kia; Denver, Sigrid; Christensen, Tove; Lassen, Jesper
Abstract: Local food has received considerable attention in recent years. It is seen as a response to increased demand for authentic foods, just as organic foods have been considered to be. It is unclear whether organic and local are two complementary or competitive trends in food consumption. This study addresses this question with a mixed methods investigation of why Danish consumers of organic products and conventional consumers of local products choose locally produced food, what values and opinions they associate with local food, and whether there are sociodemographic differences between the groups. The results show that the same values and opinions tended to motivate organic consumers and a group of committed conventional consumers of local foods. However, organic consumers were much more likely to include environmental issues in their deliberations. Another group of local-food consumers did not seem to be motivated by values and opinions when purchasing locally produced foods. Some sociodemographic differences between the groups were found: organic consumers were more likely to live in the capital than committed local consumers; to have a lengthy education than consumers of local foods; and committed local-food consumers were more likely than organic consumers to have a vocational education. The article concludes that while it is to some extent the same preference for authentic food that motivates organic and committed conventional local-food consumers to buy locally produced foods, it is at the same time different types of consumers who prefer (conventional) local food and organic food.